Effects Of Single- And Mixed-Culture Fermentation Of Reconstituted Skim Milk And Subsequent Cold Storage On Microbial Survival, Post-Acidification And Selected Metabolite Concentrations - Sadr, Maryam Molavi (2009)

(untitled)
The use of Bifidobacterium spp. in fermented milks in order to improve the microbial balance in the human gut has become very popular in recent years. The present study was carried out to investigate the effect of culture composition and storage time on microbial growth, acidification properties and formation of metabolites in fermented milks containing Bifidobacterium pseudocatenulatum G4, Streptococcus thermophilus TH4 and L. delbrueckii subsp. bulgaricus LB12, after fermentation and during 4 weeks of storage at 4 ˚C. All strains used for inoculation were in pure and mixed cultures, including all the possible combinations between them. Fermentation and lag times ranged from 266 to 743 min and 5 to 35 min in single and mixed starter cultures, respectively. The titratable acidity and pH showed similar increasing or decreasing pattern after preparation and storage of fermented milks. The least pH and highest titratable acidity during the storage period was observed with single strain of L. delbrueckii subsp. bulgaricus LB12. The highest counts of L. delbrueckii subsp. bulgaricus LB12, S. thermophilus TH4 and B. pseudocatenulatum G4 was 8.54, 8.89, and 8.52 log10 cfu/mL, respectively. In single and all mixed cultures containing B. pseudocatenulatum G4, the viable probiotic cell count remained above 7 log10 cfu/mL over 4 weeks of storage.